Is there an association between severity of illness and psychiatric symptoms in patients with chronic renal failure?. Issue 8 (14th September 2018) - Guenzani, D.; Buoli, M.; Carnevali, G. S.; Serati, M.; Messa, P.; Vettoretti, S.
Abstract: Chronic renal failure (CRF) is a frequent condition in elderly subjects, and it is associated with psychiatric comorbidity, especially depressive symptoms. Purpose of the present research was to compare patients with different severity of chronic kidney disease (CKD) in terms of psychiatric symptoms. One hundred CKD subjects were randomly selected among those attending the Department of Nephrology, University of Milan. The patients were evaluated through the following rating scales: Mini-Mental State Examination (MMSE), Beck Depression Inventory (BDI), Symptom Checklist (SCL-90), Kidney Disease Quality of Life- Short Form (KDQOL-SF) and Cumulative Illness Rating Scale (CIRS). A multivariable linear regression analysis was performed considering eGFR as continuous-dependent variable and rating scale scores as independent variables. A worse eGFR significantly correlated with the score about the effects of kidney disease on daily life ( r = 0.25, p = 0.01) and the burden of kidney disease ( r = 0.18, p = 0.05). Statistical significance of kidney disease on daily life persisted also in the final multivariate model ( t = 2.04, p = 0.04). Severity of renal dysfunction seems to influence few psychiatric outcomes, particularly those related to quality of life and daily functioning. This result might depend on the over-worrying derived from the necessity to start a renal replacement therapy in the near future.